Financial Feasibility Maps of Solar Irrigation Under Climate Change in Africa - International Food Policy Research Institute (International Food Policy Research Institute, 2025)
This dataset contains 126 maps illustrating the internal rate of return (IRR) of solar irrigation and its cost-efficiency relative to diesel irrigation under 21 different scenarios.